Using focused freewriting to stimulate ideas and foster critical thinking during prewriting - Mohd. Asraf, Ratnawati; Ahmed, Sabreena; Tan, Kok Eng (English Language Education Publishing, Brisbane, 2018)
Research suggests that writing is a useful strategy for fostering critical thinking skills among students as it requires that they think about what to write and how to organise their thoughts. Yet, students of writing often face difficulty when it comes to providing the evidence to substantiate their arguments or assertions. This paper describes how focused freewriting can be used to help ESOL students to think critically about a topic and to generate the ideas to support their arguments. In this study, nine students of a Malaysian ESOL writing course were given thought-provoking images or videos during the prewriting stages of their class and then asked to write non-stop for ten minutes about whatever that came to their minds after being shown the stimulus. This was then followed by a discussion led by the teacher on the themes that emerged from their brief write-up. The study found that focused freewriting helped the students to generate ideas more quickly and to write more fluently and independently during the prewriting stage. We posit that through focused freewriting sessions and follow-up discussions, instructors can help their students to generate ideas and to think critically about issues, hence facilitating their efforts at organising their arguments before writing academic essays.